1990
DOI: 10.1083/jcb.110.3.637
|View full text |Cite
|
Sign up to set email alerts
|

The glycophospholipid-linked folate receptor internalizes folate without entering the clathrin-coated pit endocytic pathway.

Abstract: Abstract. The folate receptor, also known as the membrane folate-binding protein, is maximally expressed on the surfaee of folate-depleted tissue culture cells and mediates the high affinity accumulation of 5-methyltetrahydrofolic acid in the cytoplasm of these cells. Recent evidence suggests that this receptor recycles during folate internalization and that it is anchored in the membrane by a glycosyl-phosphatidylinositol linkage. Using quantitative immunocytochemistry, we now show that (a) this receptor is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
227
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(239 citation statements)
references
References 42 publications
11
227
1
Order By: Relevance
“…Several studies of the endocytic pathway of folate receptors in which kidney cells, MA104, as well as other cell lines were used have indicated that caveolae are involved in folate receptor endocytosis (1,8,42,43). Other studies have shown that folate receptors are localized to clathrin-coated-pits and vesicles (2,3,22).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies of the endocytic pathway of folate receptors in which kidney cells, MA104, as well as other cell lines were used have indicated that caveolae are involved in folate receptor endocytosis (1,8,42,43). Other studies have shown that folate receptors are localized to clathrin-coated-pits and vesicles (2,3,22).…”
Section: Resultsmentioning
confidence: 99%
“…Conceptually, the folate-FBP complex might be internalized in caveolae by a process termed potocytosis, following which folate is dissociated by low pH and crosses into the cytoplasm by an anion carrier and is polyglutamylated while the FBP recycles back to the cell surface [29]. Although this concept was developed from studies with isolated monkey kidney MA104 cells [30], it is also applicable to the proposed mechanism for folate uptake by Caco-2 cells [8] and the rat kidney proximal tubule [31] in which uptake was prevented by the cleavage of membrane-bound [$H]folic acid from transfected cells and isolated rat kidney brush border membranes by phosphatidylinositol phospholipase C [8,31]. The sequence analysis of pig liver FBP might be consistent with the glycosylphosphatidylinositol anchoring system, because 9 of the 14 C-terminal residues were identical with those described in isolated human Caco-2 and KB cells ( Figure 2) [2,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, sufficient recycling machinery is available in early endosomes to allow some degree of membrane recycling. We also speculate that some type of tether may exist between these peripherally stalled vesicles and the plasma membrane that enables the return of the FR-containing endosome back to the cell surface (23,24).…”
Section: Discussionmentioning
confidence: 99%